SARS-COV-2 recombinant Receptor-Binding-Domain (RBD) induces neutralizing antibodies against variant strains of SARS-CoV-2 and SARS-CoV-1. Issue 40 (24th September 2021) - Law, John Lok Man; Logan, Michael; Joyce, Michael A.; Landi, Abdolamir; Hockman, Darren; Crawford, Kevin; Johnson, Janelle; LaChance, Gerald; Saffran, Holly A.; Shields, Justin; Hobart, Eve; Brassard, Raelynn; et al.
Abstract: SARS-CoV-2 is the etiological agent of COVID19. There are currently several licensed vaccines approved for human use and most of them target the spike protein in the virion envelope to induce protective immunity. Recently, variants that spread more quickly have emerged. There is evidence that some of these variants are less sensitive to neutralization in vitro, but it is not clear whether they can evade vaccine induced protection. In this study, we tested SARS-CoV-2 spike RBD as a vaccine antigen and explored the effect of formulation with Alum/MPLA or AddaS03 adjuvants. Our results show that RBD induces high titers of neutralizing antibodies and activates strong cellular immune responses. There is also significant cross-neutralization of variants B.1.1.7 and B.1.351 and to a lesser extent, SARS-CoV-1. These results indicate that recombinant RBD can be a viable candidate as a stand-alone vaccine or as a booster shot to diversify our strategy for COVID19 protection.